2013
DOI: 10.2147/ott.s44406
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle albumin-bound paclitaxel combined with cisplatin as the first-line treatment for metastatic esophageal squamous cell carcinoma

Abstract: Esophageal cancer is a major health hazard in many parts of the world and is often diagnosed late. The objective of this study was to explore the efficacy and safety of nanoparticle albumin-bound paclitaxel (Nab-PTX) combined with cisplatin (DDP) in patients with metastatic esophageal squamous cell carcinoma (ESCC). Patients with histologically confirmed ESCC were treated with Nab-PTX 250 mg/m2 and DDP 75 mg/m2 intravenously on day 1, every 21 days. Evaluation was performed after every two cycles of therapy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 39 publications
3
37
2
Order By: Relevance
“…Weekly nab-PC outclassed sb-PC resulting in a significantly improved overall response rate (ORR) in advanced NSCLC [17]. Moreover, the combination of nab-PC and cisplatin had already been realized as a highly effective and well-tolerated first-line treatment in metastatic ESCC [18]. Based on the hot issues in locally advanced esophageal cancer therapy, we carried out a phase II clinical study to determine the pathological response rate, efficacy and safety of preoperative neoadjuvant chemotherapy with weekly nab-PC and cisplatin in treating locally advanced ESCC.…”
Section: Introductionmentioning
confidence: 99%
“…Weekly nab-PC outclassed sb-PC resulting in a significantly improved overall response rate (ORR) in advanced NSCLC [17]. Moreover, the combination of nab-PC and cisplatin had already been realized as a highly effective and well-tolerated first-line treatment in metastatic ESCC [18]. Based on the hot issues in locally advanced esophageal cancer therapy, we carried out a phase II clinical study to determine the pathological response rate, efficacy and safety of preoperative neoadjuvant chemotherapy with weekly nab-PC and cisplatin in treating locally advanced ESCC.…”
Section: Introductionmentioning
confidence: 99%
“…However, the small patients' sample (33 patients) and subsequent treatments for most patients (87.9% patients receiving subsequent treatment after progression) may have contributed to better OS in the study (Shi, et al, 2013). In our project, albeit the differences in PFS or OS were not statistically significant for all regimens, the two endpoints tended to be better in Nab-PTX based and TPF than TP regimen.…”
Section: Discussionmentioning
confidence: 58%
“…Recently, an one-armed study illuminated the efficacy of Nab-PTX by evaluating the OS, PFS, and ORR in Chinese metastatic esophageal squamous cell cancer patients (Shi, et al, 2013), concluded with a longer median OS (15.5 months) and corresponding ORR and PFS compared with other traditional taxanes based regimens. However, the small patients' sample (33 patients) and subsequent treatments for most patients (87.9% patients receiving subsequent treatment after progression) may have contributed to better OS in the study (Shi, et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations